2020
DOI: 10.1089/hum.2020.196
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Capsid-Promoter Interactions in the Brain Translate from Rat to the Nonhuman Primate

Abstract: Recently, we established an adeno-associated virus (AAV9) capsid-promoter interaction that directly determined cellspecific gene expression across two synthetic promoters, Cbh and CBA, in the rat striatum. These studies not only expand this capsid-promoter interaction to include another promoter in the rat striatum but also establish AAV capsid-promoter interactions in the nonhuman primate brain. When AAV serotype 9 (AAV9) vectors were injected into the rat striatum, the minimal synthetic promoter JetI drove g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…This may be due to the viral subtype used (AAV2 versus AAV9), animal species (canine versus murine), or timing of treatment (3 months of age versus P1), and it is unclear what parameters are necessary for successful retinal expression via CSF delivery, including interactions between capsid and promoter. 39 Importantly, given the differences between visual processes of rodents and humans, our study will need to be validated in animal models that are more reliant on the thalamus for visual processing.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the viral subtype used (AAV2 versus AAV9), animal species (canine versus murine), or timing of treatment (3 months of age versus P1), and it is unclear what parameters are necessary for successful retinal expression via CSF delivery, including interactions between capsid and promoter. 39 Importantly, given the differences between visual processes of rodents and humans, our study will need to be validated in animal models that are more reliant on the thalamus for visual processing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous work has demonstrated that AAV administration into the parenchyma leads to extremely high levels of transgene expression close to the injection site but a vastly lower expression level in distal brain regions 43,57 . Importantly, the cell type that expresses the therapeutic protein will depend on the AAV capsid and promoter used 58 . Conversely, we showed here that the tiling behavior of MLCs expands the reach of HSPC-derived cells to the whole brain, resulting in an even and widespread (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interactions between AAV capsids and promoters driving cell type transduction regardless of virus permissivity have been recently reported in both rodent and NHPs, and these interactions include widely-used promoters such as CBA and JetI [19,20].…”
Section: Aav Landscapesmentioning
confidence: 99%